الموهوبين من منظور بيونفسي اجتماعي - غدايفي, هند; سالم, يعقوب; حميدي, شروق (جامعة الوادي - University of Eloued, 2022)
ملخص: يوصف الموهوبون بالذكاء والقدرات العالية و النجاح التعليمي و المهني، ومع ذلك، لا يعرف الكثير عن الصعوبات التي يواجهها هؤلاء الموهوبون. على وجه التحديد، حيث لديهم قدرة فكرية عالية (الدماغ المفرط) و استثارة مفرطة في مجالات مختلفة قد تعرضهم لاضطرابات نفسية معينة و أخرى اجتماعية، علاوة على حالات فسيولوجية تنطوي عليها أمراض نتيجة استجابات مناعية والتهابات متغيرة . الأطفال الموهوبين لديهم احتياجات عاطفية واجتماعية مختلفة مقارنة بأقرانهم ذوي الذكاء العادي، لأنهم عرضة لعواقب نفسية وفسيولوجية بسبب التفاعل المفرط للجهاز العصبي المركزي. فهم بأمس الحاجة للتنمية الاجتماعية والدعم الاجتماعي لتحسين من إدراكهم وتحقيق ذواتهم ليصبحوا بالغين أصحاء في الجانب البيولوجي النفسي الاجتماعي . Abstract: Gifted people are described as intelligent, highly capable, and educationally and professionally successful, however, not much is known about the difficulties these gifted face. Specifically, where they have a high intellectual capacity (hyper brain) and excessive excitability in different areas may expose them to certain psychological and other social disorders, as well as physiological states involved in diseases as a result of altered immune and inflammatory .responses Gifted children have different emotional and social needs compared to their peers of normal intelligence, because they .are vulnerable to psychological and physiological consequences due to an overreactivity of the central nervous system They are in dire need of social development and social support to improve their awareness and self-actualization to become healthy adults in the biological, psychosocial aspect.
مقال
Keywords: الطالب الموهوب ، التنمية الاجتماعية; studentSocial development, talented student